2016
DOI: 10.4314/wsa.v42i4.11
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of conventional water treatment in removing <i>Ceratium furcoides</i> (Levander) Langhans, <i>Microcystis</i> sp. and microcystins

Abstract: Algal blooms are a global problem due to various negative effects that can compromise water quality, such as the production of metabolites that are responsible for odour, colour, taste and toxins. In drinking water supplies algae can reduce the aesthetics of potable water when not readily removed by conventional water treatment processes. One of the major challenges in water treatment is the removal of cells without leading to lysis and the consequent release of dissolved metabolites in the water. The Maestra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
9
0
6
Order By: Relevance
“…In most cases, the invaded freshwater systems have presented historical blooms of cyanobacteria and the arrival of Ceratium seems to overturn the cyanobacterial dominance (Nishimura et al 2015;Cavalcante et al 2016;Crossetti et al 2019). In other cases, C. furcoides blooms were found accompanied by cyanobacterial blooms (Silva et al 2012;Almeida et al 2016). Almanza et al (2016) found that the phytoplankton community presented lower diversity and species richness during the colonization process performed by C. furcoides in a Chilean eutrophic lake.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the invaded freshwater systems have presented historical blooms of cyanobacteria and the arrival of Ceratium seems to overturn the cyanobacterial dominance (Nishimura et al 2015;Cavalcante et al 2016;Crossetti et al 2019). In other cases, C. furcoides blooms were found accompanied by cyanobacterial blooms (Silva et al 2012;Almeida et al 2016). Almanza et al (2016) found that the phytoplankton community presented lower diversity and species richness during the colonization process performed by C. furcoides in a Chilean eutrophic lake.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de não tóxicos, estes dinoflagelados são impalatáveis devido à sua morfologia e, sua presença em grandes quantidades pode ser prejudicial ao ambiente pelo esgotamento de recursos e redução do oxigênio (Matsumura-Tundisi et al 2010). Além disso, Ceratium é reconhecido como causador de sabor e odor à água, sendo também responsável por situações indesejadas ao sistema de abastecimento, como problemas de reserva, distribuição e tratamento, causando o encarecimento do processo (Van Der Walt 2011, Almeida et al 2016, Morales 2016. Isto porque os tratamentos convencionais de água não são adequados sob altas densidades de Ceratium, uma vez que sua presença pode interromper processos de coagulação, floculação e sedimentação, além de provocar o entupimento dos filtros (Ewerts et al 2013).…”
Section: Introductionunclassified
“…Entre as principais causas do aumento da eutrofização está o aporte das descargas de esgotos domésticos e industriais dos centros urbanos, sem tratamento adequado, e de fontes difusas provindas de regiões agriculturá-veis. Devido a essa riqueza nutricional, o surgimento de espécies de cianobactérias em ambientes eutrofizados tem aumentado, causando a formação de florações em diversas regiões no Brasil (ALMEIDA et al, 2016;LINS et al, 2016).…”
Section: Eutrofização E Florações De Cianobactérias No Brasilunclassified
“…Esse fato assume crescente relevância uma vez que a maioria desses florescimentos de cianobactérias tem demonstrado o potencial tóxico de muitas de suas espécies no Brasil (AZEVEDO & VASCONCELOS, 2008;ALMEIDA et al, 2016;LINS et al, 2016).…”
Section: Eutrofização E Florações De Cianobactérias No Brasilunclassified
See 1 more Smart Citation